Purification of an Ion-Stimulated Adenosine Triphosphatase from Plant Roots: Association with Plasma Membranes - Hodges, T. K. (1972)
A membrane-bound adenosine triphosphatase (EC 3.6.1.3) that requires Mg(++) and that is stimulated by monovalent ions has been purified 7- to 8-fold from homogenates of oat (Avena sativa L. Cult. Goodfield) roots by discontinuous sucrose-gradient centrifugation. The enzyme was substrate specific; adenosine triphosphate was hydrolyzed 25 times more rapidly than other nucleoside triphosphates. The membrane fraction containing adenosine triphosphatase was enriched in plasma membranes, which were identified by the presence of a glucan synthetase (EC 2.4.1.12), a high sterol to phospholipid ratio, and by a stain consisting of periodic acid, chromic acid, and phosphotungstic acid that is specific for plant plasma membranes. Oat-root plasma membranes and the associated adenosine triphosphatase were purified on either a 6-layer discontinuous sucrose gradient or on a simplified gradient consisting of only two sucrose layers. These results represent the first demonstration that plant plasma membranes contain an adenosine triphosphatase that is activated by monovalent ions, and this finding further implicates the enzyme in the absorption of inorganic ions by plant roots.